2005
DOI: 10.1152/ajpheart.00892.2004
|View full text |Cite
|
Sign up to set email alerts
|

Positive inotropic and negative lusitropic effects of endothelin receptor agonism in vivo

Abstract: -The endothelin (ET) system is involved in the regulation of myocardial function in health as well as in several diseases, such as congestive heart failure, myocardial infarction, and septic myocardial depression. Conflicting results have been reported regarding the acute contractile properties of ET-1. We therefore investigated the effects of intracoronary infusions of ET-1 and of the selective ETB receptor-selective agonist sarafotoxin 6c with increasing doses in anesthetized pigs. Myocardial effects were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
15
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 48 publications
7
15
1
Order By: Relevance
“…Previous reports showed that ET-1 elicits the negative inotropic myocardial effect from ET B receptor activation (Konrad et al, 2005), and that this requires an intact endocardial endothelium and is mediated by nitric oxide and prostaglandins (Leite-Moreira and Brás-Silva, 2004). The present study observed that ET-1-activated atrial ANP secretion was completely blocked by BQ788, an ET B receptor inhibitor, while the ET A receptor inhibitor BQ123 only slightly attenuated the effect of ET-1-activated ANP secretion.…”
Section: Discussionsupporting
confidence: 57%
“…Previous reports showed that ET-1 elicits the negative inotropic myocardial effect from ET B receptor activation (Konrad et al, 2005), and that this requires an intact endocardial endothelium and is mediated by nitric oxide and prostaglandins (Leite-Moreira and Brás-Silva, 2004). The present study observed that ET-1-activated atrial ANP secretion was completely blocked by BQ788, an ET B receptor inhibitor, while the ET A receptor inhibitor BQ123 only slightly attenuated the effect of ET-1-activated ANP secretion.…”
Section: Discussionsupporting
confidence: 57%
“…This observation supports the in vitro finding that NOS inhibition enhances the inotropic response to ET-1 (Kinnunen 2000). Exogenous ET-1 infusion may increase the in vivo cardiac contractility significantly, an effect that can be prevented by ET-A receptor antagonist pretreatment (Konrad 2005). In our study, the plasma ET-1 level gradually increased up to the end of the experiments, which may suggest that, after induction by NNA treatment, it was continuously replaced from the cellular sources.…”
Section: No Effects On Cardiac Contractilitysupporting
confidence: 91%
“…Exogenous ET-1 infusion may increase the in vivo cardiac contractility significantly, an effect that can be prevented by ET-A receptor antagonist pretreatment (Konrad 2005). The results revealed that the plasma level of ET-1 increased significantly in this setup too, and the peptide induced 37 positive inotropy through the activation of ET-A receptors (Eszlári 2008).…”
Section: Discussion Of Study IImentioning
confidence: 79%
“…However, the finding of delayed benefit was based on a post hoc analysis of a small number of events observed in a subgroup of patients-characteristics that increase the likelihood of the play of chance. No biphasic response was seen in a dose-ranging trial with the more endothelin type A (ET A ) receptor-selective antagonist enrasentan (18), which noted an excess early risk of worsening heart failure, which persisted for the duration of follow-up (Figure 5).The mechanisms leading to early worsening heart failure in patients treated with endothelin antagonists(17,19,25) have not been fully elucidated.Receptor antagonism may interfere with the positive inotropic and negative lusitropic effects of endothelin(26) or may have adverse effects on neurohormonal activation or cardiac remodeling(27). In addition, endothelin receptor antagonists dilate the pulmonary arterioles(28), and thus, may interfere with the restraint that pulmonary vasoconstriction normally exerts on blood flow into the lungs and the transudation of fluid into alveoli when pulmonary venous pressures are increased(29,30).In the current trial and earlier studies(17,19,21), however, early worsening heart failure was related to fluid retention.…”
mentioning
confidence: 99%